Young female with repeated chest and gastrointestinal infections - Ul Ain, Qurat; Rasool, Rabia; Afsheen, Saliha (Infectious Diseases Journal of Pakistan, 2024)
Common variable immunodeficiency disorder (CVID) is a primary immunodeficiency disorder characterised by reduced serum levels of immunoglobulin G (IgG), along with immunoglobulin A (IgA) and/or immunoglobulin M (IgM).1 The range of clinical manifestations is broad, including acute and chronic infections, inflammatory and autoimmune disease, and an increased incidence of cancer and lymphoma.2 We present a case of a young female with bronchial asthma, repeated chest infections, and a prolonged episode of gastroenteritis. After a detailed history, examination, and investigations, she was diagnosed with CVID. She was managed with IV fluids, antibiotics, and antiprotozoal medications. After one month of follow-up, she was doing well. Keywords: Immunodeficiency, Immunoglobulins, CVID, Respiratory tract infection, IgA, IgG, IgM, asthma, gastroenteritis